Radical polymerization by a supramolecular catalyst: cyclodextrin with a RAFT reagent - Koyanagi, Kohei; Takashima, Yoshinori; Nakamura, Takashi; Yamaguchi, Hiroyasu; Harada, Akira (Beilstein Journal of Organic Chemistry, 2016)
Supramolecular catalysts have received a great deal of attention because they improve the selectivity and efficiency of reactions. Catalysts with host molecules exhibit specific reaction properties and recognize substrates via host–guest interactions. Here, we examined radical polymerization reactions with a chain transfer agent (CTA) that has α-cyclodextrin (α-CD) as a host molecule (α-CD-CTA). Prior to the polymerization of N,N-dimethylacrylamide (DMA), we investigated the complex formation of α-CD with DMA. Single X-ray analysis demonstrated that α-CD includes DMA inside its cavity. When DMA was polymerized in the presence of α-CD-CTA using 2,2'-azobis[2-(2-imidazolin-2-yl)propane dihydrochloride (VA-044) as an initiator in an aqueous solution, poly(DMA) was obtained in good yield and with narrow molecular weight distribution. In contrast, the polymerization of DMA without α-CD-CTA produced more widely distributed polymers. In the presence of 1,6-hexanediol (C6 diol) which works as a competitive molecule by being included in the α-CD cavity, the reaction yield was lower than that without C6 diol.
Keywords: cyclodextrin; radical polymerization; RAFT polymerization; substrate recognition site; supramolecular catalyst